Study on Contact Force and Transmission Accuracy of Cycloidal Wheel with Exponential Modification - Chen Xinwen; Zhu Min; Wang Qiliang (Jixie chuandong)
RV reducer plays a dominant role in the field of robots because of its advantages of high accuracy，high efficiency and small size.Cycloid wheel，as the key component of RV reducer，directly affects the performance of the transmission system of RV reducer.In order to improve the meshing performance of cycloidal pin wheel，the radius of needle teeth is constructed as an exponential function of the rotation angle for modification，and the profile equation after modification is established.The tooth profile curve and curvature radius of cycloidal wheel before and after modification are compared with examples.The contact pressure and transmission error between cycloid wheel and pin teeth are calculated when the crank rotates from 0°~360°.The exponential function modification maintains the theoretical tooth profile curve in the working section of cycloidal gear，overcomes the problem of large modification amount in traditional modification method，ensures the meshing stability，and improves the strength and transmission accuracy of cycloidal wheel.